Sclerosing cholangitis. - Martins, E; Chapman, R (2000)
Primary sclerosing cholangitis is a chronic cholestatic liver disease of unknown etiology. Immunogenetic factors are considered important in its pathogenesis. The genetic susceptibility to primary sclerosing cholangitis is associated, in part, with the HLA HLA-DRB1, DQA1, DQB1 haplotype. Liver histology in primary sclerosing cholangitis is characterized by a portal inflammatory infiltrate mostly composed of memory T cells. Many patients eventually will develop cholangiocarcinoma, and inactivation of the p16 tumor-suppressor gene might be involved in neoplastic transformation. Alcohol consumption might be a risk factor for cholangiocarcinoma, and, in some patients, elevation of serum CA19-9 marks the neoplastic transformation. To date, no medical treatment has been proven effective. Endoscopic therapy might be useful in some patients, but controlled studies are lacking. Liver transplantation remains the only effective treatment. Posttransplant survival and quality of life are continuously improving despite the fact that the disease may recur in some patients after transplantation. Nevertheless, patient selection and timing of indication for liver transplantation remain uncertain.